Frankétienne poto-mitan - Yves Chemla (Continents manuscrits)
The earthquake that considerably bereaved the city and the region of Port-au-Prince in January 2010 led to the reinforcement of buildings that were not considered dangerous and doomed to destruction. The house of the writer and painter Frankétienne was thus repaired and consolidated with the help of concrete pillars, quickly transformed into pictorial surfaces and support for sentences by the artist. This monumental dimension that shapes the resistance against all the recurring disasters in Haiti takes place inside the domestic space of the Étienne family and the work space of the writer.